2007
DOI: 10.20870/oeno-one.2007.41.2.853
|View full text |Cite
|
Sign up to set email alerts
|

Response of ungrafted and grafted grapevine cultivans and rootstocks (<em>Vitis</em> sp.) to water stress

Abstract: <p style="text-align: justify;"><strong>Aims</strong>: The responses of two Vitis vinifera cultivars (Cardinal and Superior Seedless) and two rootstocks (110R and SO4) to drought, the effect of grafting and the interactions of scion/rootstock were investigated.</p><p style="text-align: justify;"><strong>Methods and results</strong>: The vines were subjected to a progressive water stress in greenhouse controlled conditions. At the end of the water stress treatments, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
(38 reference statements)
2
18
0
1
Order By: Relevance
“…In our study, leaf area and the number of leaves were not negatively affected by the water deficit, in contrast to the results of Gomez-del-Campo et al [20] where less leaf area was produced under water limiting conditions and the number of leaves was lower than under well-watered conditions. Plant growth, indicated by annual dry mass production, decreased, when the deficit was more severe which is in accordance with the study of Toumi et al [19]. Within the study of Tardieu et al [48], SLA was reported to decrease, if environmental conditions led to greater reduction of growth than on photosynthesis [48].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, leaf area and the number of leaves were not negatively affected by the water deficit, in contrast to the results of Gomez-del-Campo et al [20] where less leaf area was produced under water limiting conditions and the number of leaves was lower than under well-watered conditions. Plant growth, indicated by annual dry mass production, decreased, when the deficit was more severe which is in accordance with the study of Toumi et al [19]. Within the study of Tardieu et al [48], SLA was reported to decrease, if environmental conditions led to greater reduction of growth than on photosynthesis [48].…”
Section: Discussionsupporting
confidence: 88%
“…In most studies investigating the influence of water deficiency on plant growth and the adaptation of plants to the limited availability of soil water, it was observed that leaf area, dry matter, and number of leaves decreased in response to water limitation [19]. In our study, leaf area and the number of leaves were not negatively affected by the water deficit, in contrast to the results of Gomez-del-Campo et al [20] where less leaf area was produced under water limiting conditions and the number of leaves was lower than under well-watered conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other authors have reported a sustained decrease in F v /F m of dark-adapted grapevine leaves along with an increase in F 0 , suggesting the occurrence of photoinhibitory damage in response to high temperature and drought (Gamon and Pearcy 1989;Zulini et al 2007). Moreover, studies regarding the effect of rootstock on grapevine physiological performance in a stressful environment appear to be interlinked with photochemical changes and stomatal limitations (Iacono et al 1998;Toumi et al 2007) Nonetheless, the combined effect of water deficit, high temperature, and light are presumably the main constraints for photosynthesis, particularly under severe soil water deficits (Flexas et al 1998). Chlorophyll degradation is also a consequence of summer stress and appears to be associated with the production of reactive oxygen species (ROS) (Camejo et al 2006;Guo et al 2006).…”
Section: Effects On Photosynthesismentioning
confidence: 99%
“…Furthermore, many studies showed that clusters exposed to sunlight have lower TA . However, it should be taken into account that no direct comparisons between own‐rooted and grafted vines can be conducted due to different adaptation to environmental stresses …”
Section: Resultsmentioning
confidence: 99%